MUHAMMAD ABDUH SEBAGAI MUFASSIR - Hasiah, Hasiah (IAIN Padangsidimpuan, 2013)
Muhammad Abduh as renewal leader has managed to give birth to the method of interpretation that he is also no less sharp with the other commentators. He creates a new way of interpreting the verses of the Qur'an